Quercetin Alleviates Pulmonary Fibrosis in Mice Exposed to Silica by Inhibiting Macrophage Senescence - Geng, Fei; Xu, Mengying; Zhao, Lan; Zhang, Haoming; Li, Jiarui; Jin, Fuyu; Li, Yaqian; Li, Tian; Yang, Xinyu; Li, Shifeng; Gao, Xuemin; Cai, Wenchen; et al. (Frontiers in Pharmacology, 2022)
Quercetin exerts anti-inflammatory, anti-oxidant, and other protective effects. Previous studies have shown that senescent cells, such as fibroblasts and type II airway epithelial cells, are strongly implicated in the development of pulmonary fibrosis pathology. However, the role of senescent macrophages during this development remains unclear. We investigated the effects of quercetin on macrophage senescence and pulmonary fibrosis, and explored underlying mechanisms. Mice were randomized to six model groups. Vitro model was also established by culturing RAW264.7 macrophages with silica (SiO2). We examined the effects of quercetin on fibrosis, senescence-associated β-galactosidase (SA-β-Gal) activity, and senescence-specific genes (p16, p21, and p53). We showed that quercetin reduced pulmonary fibrosis and inhibited extracellular matrix (ECM) formation. Quercetin also attenuated macrophage senescence induced by SiO2 both in vitro and in vivo. Quercetin also significantly decreased expression of the senescence-associated secretory phenotype (SASP), including proinflammatory factors (interleukin-1α (Il-1α), Il-6, tumor necrosis factor-α (TNF-α), and transforming growth factor-β1 (TGF-β1)) and matrix metalloproteinases (MMP2, MMP9, and MMP12). Collectively, quercetin mediated its anti-fibrotic effects by inhibiting macrophage senescence, possibly via SASP.